Grammer Grove hawk watch, 1999, Beth Proescholdt - Proescholdt, Bethet al (1999)
An annotated list of birds sighted by Beth Proescholdt. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed/flatbed